Exploring sentiments and topics in Extended Reality learning environments: A comparative study. - Hosam Al-Samarraie; Samer Muthana Sarsam; Ahmed Ibrahim Alzahrani; Hanan Aldowah (PLoS ONE)
This study explored online users' sentiments about the use and application of Extended Reality (XR) in higher education. X social media platform was used as the main source for assessing users' perceptions of XR in teaching and learning. A topic modelling approach was used to identify and compare main themes and topics in relation to the use of Virtual Reality (VR) and Augmented Reality (AR)/Mixed Reality (MR). The sentiment and polarity of each topic were assessed and compared across these technologies. The results revealed three themes for VR (self-directed learning, creativity-promoting environments, and challenges and concerns) and three themes for AR/MR (guided and oriented learning experience, playful and flexible learning experience, and challenges and concerns). The results also demonstrated significant differences in users' sentiments, with VR use in higher education achieving higher positivity, anticipation, trust, and joy compared to AR/MR. Findings from this study are unique in the sense that they offer a comparative perspective on XR inclusion in university teaching and learning. The findings can direct policy makers in higher education about the suitability and feasibility of using certain XR technologies in facilitating their digital transformation goals.